A review on polyamide thin film nanocomposite (TFN) membranes: History, applications, challenges and approaches. (1st September 2015) - Lau, W.J.; Gray, Stephen; Matsuura, T.; Emadzadeh, D.; Paul Chen, J.; Ismail, A.F.
Abstract: This review focuses on the development of polyamide (PA) thin film nanocomposite (TFN) membranes for various aqueous media-based separation processes such as nanofiltration, reverse osmosis and forward osmosis since the concept of TFN was introduced in year 2007. Although the total number of published TFN articles falls far short of the articles of the well-known thin film composite (TFC) membranes, its growth rate is significant, particularly since 2012. Generally, by incorporating an appropriate amount of nanofiller into a thin selective PA layer of a composite membrane, one could produce TFN membranes with enhanced separation characteristics as compared to the conventional TFC membrane. For certain cases, the resulting TFN membranes demonstrate not only excellent antifouling resistance and/or greater antibacterial effect, but also possibly overcome the trade-off effect between water permeability and solute selectivity. Furthermore, this review attempts to give the readers insights into the difficulties of incorporating inorganic nanomaterials into the organic PA layer whose thickness usually falls in a range of several-hundred nanometers. It is also intended to show new possible approaches to overcome these challenges in TFN membrane fabrication. Graphical abstract: Highlights: Comprehensive review on the development of TFN membrane for water treatment. Potential of TFN membrane in overcoming permeability/selectivity trade-off effect. Nanofiller characteristics/amount and IP condition that affect TFN properties. Innovative approaches to overcome TFN fabrication challenges.